(3QMdI Edi CQV GdMHTIs - (3GdMSf Hf CMeO GdMjej GdTHGej, GdbGVj TQa GdOjfs ((3CMeO Hf YHO Gddg Hf MSfi Hf Ydi Hf eMeO Hf Ydi GdgGOi GdgGOhi s)
(3ChdgG (B:s
(3hHYO aEfg SCdfi ef hLg Edi s
(3BNQgG (B:s
(3jLQi ef JMJgG GdCfgGQ hgGgfG jfJgi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdLZQGajG h GdHdOGfs